Adoption and welfare impact of improved food legume technologies in Bale Highlands of Ethiopia: Intra and inter-household empirical analysis - Degefu, Z. (Haramaya University, 2016)
This study was designed to investigate the adoption of improved food legume technologies and welfare impacts of improved food legume varieties specifically on income, consumption expenditure and calorie intake in Bale highlands of Ethiopia. The study focused particularly on the identification of factors determining adoption of improved food legume technologies, evaluation of welfare impacts of adoption status and intensity of improved food legume varieties, identifying intra-household impact dynamics due to adoption of improved legume varieties and spotting out the major challenges and opportunities faced by smallholders in their adoption of improved food legume technologies.. This study used cross sectional data that acquired from a total of 600 households, which were randomly and proportionately sampled from 12 major legume producer kebeles in 3 districts of Bale highlands by using three-stage sampling technique. Probit and Clog-log binary model were estimated to identify the underlying factors that determine adoption of improved food legume varieties; and fertilizer and pesticide, respectively and separately. PSM model was estimated to evaluate the welfare impacts of adoption of improved food legume varieties. In addition, continuous treatment effects model (GPS) was also employed to estimate the welfare impact of intensity of adoption by discarding non-adopters from the analysis. The results from probit and clog-log indicate that age, livestock holding, farm size, membership in farmers cooperatives, contact with agricultural research center, household head participation in off-farm activity, distance from agricultural extension office and main market; and location (district dummy) were factors that significantly determine farmers decision to adopt improved food legume technologies. The study also indicates that adoption of improved food legume technologies can motivate farmers to shift from the monocropping system to diversified one, improve income since they fetch higher prices than common cereals and they are the major source of protein for the household who cannot acquire it from animal products. However, adoption of improved food legume technologies is highly constrained by labor-intensive nature of the production, lack of improved food legume technologies especially water logging tolerant varieties and market irregularities. The outputs from PSM indicate that adoption of improved food legume varieties has positive and significant impact on the income and the adopter receive 25% higher income than non-adopter. The intra household analysis indicated that households with productive labor force receive better treatment effect while households with economically dependents female members receive considerably lower treatment effects from adoption of improved food legume varieties, suggesting the prevalent intra-household differences. The result of GPS also confirms the positive effect of intensity of adoption on income, consumption expenditure and calorie intake. The results generally suggests the need to design interventions enhancing adoption of food legume technologies focusing on improving adoption rates and minimizing intra household difference in income.